THE ROLE OF ONLINE PROMOTION, WORD OF MOUTH, AND PRODUCT QUALITY IN INCREASING BUYING INTEREST SALE PISANG AROMA RASA - Giri Pamungkas; Sutianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The purpose of this study is to analyze online promotion, word of mouth, product quality on buying interest Sale Pisang Aroma Rasa. The population used in this study is potential people who are interested in buying Sale Pisang Aroma Rasa in Grobogan City. The Purposive Sampling method was used to select 90 samples for this study. Data collection was carried out using a questionnaire. This study uses various statistical tools, including multiple linear regression, reliability and validity test, t-test, F-test, and determination coefficient. Product quality, advertising, and word of mouth all have a good and great influence on buying interest Pisang Aroma Rasa in the City Grobogan. Keywords: promosi online, word of mouth